2021
DOI: 10.3390/ijms22168760
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Release of Paclitaxel and Imatinib from Core–Shell Microparticles Prepared by Coaxial Electrospray for Vaginal Therapy of Cervical Cancer

Abstract: To optimize the anti-tumor efficacy of combination therapy with paclitaxel (PTX) and imatinib (IMN), we used coaxial electrospray to prepare sequential-release core–shell microparticles composed of a PTX-loaded sodium hyaluronate outer layer and an IMN-loaded PLGA core. The morphology, size distribution, drug loading, differential scanning calorimetry (DSC), Fourier transform infrared spectra (FTIR), in vitro release, PLGA degradation, cellular growth inhibition, in vivo vaginal retention, anti-tumor efficacy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…One of the most difficult challenges in pharmaceutics is the dissolution and effective delivery of poorly water-soluble APIs [ 73 , 74 ]. The existence state of these poorly water-soluble APIs in the raw powders is mainly crystalline, which makes them difficult to disperse in the body fluids.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most difficult challenges in pharmaceutics is the dissolution and effective delivery of poorly water-soluble APIs [ 73 , 74 ]. The existence state of these poorly water-soluble APIs in the raw powders is mainly crystalline, which makes them difficult to disperse in the body fluids.…”
Section: Resultsmentioning
confidence: 99%
“…182,183 Furthermore, numerous studies have explored the use of electrosprayed formulations to improve the delivery of drugs such as paclitaxel, doxorubicin, methotrexate, gemcitabine, camptothecin, docetaxel, cisplatin, and etoposide. 153,155,[184][185][186][187][188][189] Other approaches, such as PLGA porous beads as microscaffolds 190 and oxygen release systems, 107 have also been investigated for cardiomyoplasty. Injectable hydrogels combining drug-loaded alginate microspheres with PLGA-PEG-PLGA hydrogels have also been developed.…”
Section: Injectable Drug Deliverymentioning
confidence: 99%
“…Khare et al 182 created electrosprayed lipid nanoparticles for siRNA delivery, while Swetledge et al 183 formulated polymeric nanoparticles for ocular drug delivery, resulting in improved cellular uptake, gene silencing, bioavailability, and sustained release 182,183 . Furthermore, numerous studies have explored the use of electrosprayed formulations to improve the delivery of drugs such as paclitaxel, doxorubicin, methotrexate, gemcitabine, camptothecin, docetaxel, cisplatin, and etoposide 153,155,184–189 . Other approaches, such as PLGA porous beads as microscaffolds 190 and oxygen release systems, 107 have also been investigated for cardiomyoplasty.…”
Section: Electrospray Nanoparticles For Biomedical Applicationmentioning
confidence: 99%
“…The association of two or more drugs to improve the treatment of cancer patients can be a challenge, as interactions between drugs may occur. To associate paclitaxel (PTX) and imatinib (IMN), Liu et al [ 25 ] prepared polymeric microcapsules with external enclosure of PTX-loading hyaluronate and IMN-loading PLGA nucleus, to be vaginally administered for cervical cancer treatment. The in vitro release study showed a two-step release pattern: in the former step approximately 80% of PTX contained in the outer layer was quickly released, while in the latter, of the sustained type, approximately 90% of IMN was released within 7 days.…”
Section: Polymeric Microparticles In Biological Testsmentioning
confidence: 99%